2015
DOI: 10.4149/bll_2015_008
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and hepatoprotective activity of ethanolic root extract of Taraxacum Syriacum Boiss against acetaminophen intoxication in rats

Abstract: Abstract:Aim: In the present study, the role of ethanol extract of root of Taraxacum Syriacum Boiss (TSBE) against hepatotoxicity caused by acetaminophen (APAP) was studied. Methods: The chemical composition of roots of Taraxacum Syriacum Boiss was analyzed by SPME-GC/MS method. Hepatocellular injuries induced by acetaminophen (APAP) were assessed by liver histology, serum aminotransferase activities, antioxidant enzymes activity and lipid peroxidation in liver tissue. Results: TSBE was observed to exhibit hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
5
0
3
Order By: Relevance
“…Anti-oxidant treatment had been widely used in the treatment of the noxious effects of heavy metal toxicity [8]. In the present study, the protective role of combined selenium and P. granatum against liver injury induced by arsenic in rats had been studied by determining their effects on some oxidative stress and inflammatory markers in addition to Nrf2 gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-oxidant treatment had been widely used in the treatment of the noxious effects of heavy metal toxicity [8]. In the present study, the protective role of combined selenium and P. granatum against liver injury induced by arsenic in rats had been studied by determining their effects on some oxidative stress and inflammatory markers in addition to Nrf2 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the enzymes regulated by Nrf2 transcription factor, thioredoxin reductase (TrxR) is a cellular antioxidant containing selenocysteine in its C-terminal redox center, resulting in increase in total anti-oxidant capacity [7]. Growing body of evidences highlights the anti-oxidant ameliorative role on the free radical generation that occurs in heavy metal toxicity [8]. Selenium, an essential dietary trace element for mammals, is a cofactor of glutathione peroxidase (GSH-Px), an anti-oxidant enzyme that protects lipids and macromolecules in the liver cell intracellular and cellular membranes against oxidative damage generated by reactive oxygen species (ROS) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The plant extracts alone in KRHB did not show any toxicity on liver tissue over the concentrations we studied. In a recent study carried out by Nazari and coauthors (2015), it has been found that ethanolic root extract of Taraxacum Syriacum Boiss can exert hepatoprotective activity against liver toxicity induced by acetaminophen (APAP) intoxication in rats [ 34 ]. The authors believe that the mechanism through which the extract protects the liver from the oxidative stress caused by APAP is due to its antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…Embora existam diversas vias de administração, nos trabalhos selecionados para esta revisão a via oral e intraperitoneal foram as únicas citadas. Dos estudos, 18 utilizaram a via peritoneal (NAZARI et al,2015;MEHRA et al, 2016;ELBE et al, 2018). Essa via de administração é fácil de realizar em animais de laboratório e garante uma maior absorção que a via oral.…”
Section: Via De Administraçãounclassified